Studi Komparatif Konsep Ketuhanan Islam dan Agama Adam pada Komunitas Samin - Mohammad Rosyid (Universitas Islam Negeri Mataram, 2012)
One of the problems that disturb the harmony between religious communities is a lack of understanding of the majority (mainstream) religion about the local religion, and vice versa. This article aims to develop such inter-religious understanding by comparing between Islam and the religion of Adam, a local religion of Samin community. The comparative study was made within the scope of the concept of God in both religions. This study found that the understanding between Islam the religion of Adam about the concept of God is essential in common. God called Allah (in Islam) and Yai (in the religion of Adam) are equally perceived as condescendent, an only single power, and the Almighty. Both communities also share Adam as the first man in the world. So, it is not proportional if the public ridicule Samin community with atheist stigma.